Students' Problem Behaviors as Sources of Teacher Stress in Special Needs Schools for Individuals With Intellectual Disabilities - Amstad, Meta; Müller, Christoph M. (Frontiers in Education, 2020)
Students with intellectual disabilities in special needs schools often exhibit high levels of problem behaviors. Besides the challenges such behaviors present for the students themselves, their peers, and their caregivers, problem behaviors can also be a source of stress for teachers. However, less is known on the degree to which different types of problem behaviors are perceived as stressful in special needs schools for students with intellectual disabilities. Using paper-pencil questionnaires, 295 special needs school teachers (47.81 years, SD = 10.49; 83.4% female) in Switzerland ranked the perceived stressfulness (from 0 = not stressful to 3 = very stressful) of 93 student behaviors. These 93 behavior descriptions stemmed from the Developmental Behavior Checklist (Einfeld & Tonge, 1995). Results suggest behaviors endangering the student or others, such as kicking, hitting, biting, or talking about suicide, were rated as most stressful. Behaviors from the domain disruptive/antisocial behaviors were reported as most stressful and behaviors from the domain of communication disturbances as least stressful. Implications for work-related stress prevention in relation to different types of student problem behaviors for special needs school teachers are discussed.